Medical Mission And Rural Health Transformation: A Historical Study Of Christian Missionary Healthcare Work In Villupuram (1880–1970) (Journal of Namibian Studies : History Politics Culture, 2023)
This study investigates the long-term impact of Christian missionary medical work in Villupuram between 1880 and 1970, examining faith-based health initiatives contributed to the evolution of rural healthcare in colonial and early post-independence Tamil Nadu. Anchored in archival records, missionary hospital reports, district gazetteers, and oral testimonies, the research focuses on the American Arcot Mission’s medical outreach, including its establishment of dispensaries, maternity wards, leprosy care units, and training schools for nurses and midwives. Far from functioning solely as vehicles of evangelism, these medical missions engaged directly with the structural deficiencies in rural health infrastructure. This research argues that Christian medical missions in Villupuram were not marginal auxiliaries to evangelism but essential players in the historical transformation of rural health. Their hybrid legacy—combining Christian charity, scientific medicine, and vernacular outreach—helped redefine the meaning and delivery of healthcare in Tamil Nadu’s interior regions.